OPORTUNIST AND EFFICIENT PERSPECTIVE OF MANAGEMENT BASED ON THE MOTIVATIONAL ASPECTS THAT BASED ON IT - Putu Yudha Asteria Putri, Komang Adi Kurniawan Saputra (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
A common phenomenon is that users tend to focus on the amount of profit stated in the financial statements compared to other figures. This is one of the things that triggers earnings management carried out by managers in the company. Earnings management can be seen from two different perspectives, namely an opportunistic perspective (prioritizing personal interests) and an efficient perspective (prioritizing the interests of the company). This article is a collection of various literature reviews aimed at investigating the opportunist perspective and efficient management based on the underlying motivational aspects. Theories that underlie the occurrence of earnings management include agency theory, signaling theory, and Positive Accounting Theory (PAT). Based on several previous studies, Opportunistic perspective of management can be explained by agency theory and bonus plan hypothesis in PAT, while the perspective of efficient management can be explained by signaling theory and debt covenant hypothesis and political cost in PAT. Many things motivate managers to do earnings management. From an opportunist perspective, earnings management is carried out because of the motivation for bonuses and job security. On the other hand, earnings management is also classified as efficient as a result of the manager’s motivation regarding debt agreements, reducing political costs, IPOs, increasing market value, and avoiding the possibility of bankruptcy in the company. Meanwhile, the efficient management perspective can be explained by signaling theory and debt covenant hypothesis and political cost in PAT. Many things motivate managers to do earnings management. From an opportunistic perspective, earnings management is carried out because of the motivation for bonuses and job security. On the other hand, earnings management is also classified as efficient as a result of the manager’s motivation regarding debt agreements, reducing political costs, IPOs, increasing market value, and avoiding the possibility of bankruptcy in the company. Meanwhile, the perspective of efficient management can be explained by signaling theory and debt covenant hypothesis and political cost in PAT. Many things motivate managers to do earnings management. From an opportunistic perspective, earnings management is carried out because of the motivation for bonuses and job security. On the other hand, earnings management is also classified as efficient as a result of the manager’s motivation regarding debt agreements, reducing political costs, IPOs, increasing market value, and avoiding the possibility of bankruptcy in the company.